Reasons and Motives for the Emergence of the Hermeneutic Approach Contemporary for the Holy Quran - Ghanm Hameed Ibrahim; Idrees Qader Hamadameen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The enemies of Islam have realized that Muslims will not accept the taking of their religion, and the interpretation of the words of their Allah from them; Therefore, they handed over the flag to some of their students, or Muslims influenced by their culture, in order to distort the meanings of the words of Allah, and to invent meanings that did not occur to the people of all the preferred centuries, under the pretext of (contemporary reading of religious texts). The reasons are the lack of a precise or general scientific specialization in Islamic sciences, as they studied from non-Islamic scholars and universities; Therefore, they look at the Book of God with a free view that does not adhere to any of the principles of interpretation and its rules. The more a society rises and its life develops, the horizon expands and the mind deepens in penetrating the basic facts of religion. Renewing the religion for them does not mean returning to the forsaken of religion, and reminding people of what they have forgotten.They exaggerated in glorifying the mind, making it the first principle of Islam. the Orientalist movement are among the channels through which these people got to know the West. He made them the focus of attention, leaders of ideas, and leaders of innovation and development in the interpretation of religious texts.